2019
DOI: 10.1097/01.ogx.0000580484.27329.5a
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Interval Cytoreductive Surgery With Hyperthermic Intraperitoneal Chemotherapy in Stage III Ovarian Cancer on the Basis of a Randomized Phase III Trial

Abstract: PURPOSE In the randomized open-label phase III OVHIPEC trial, the addition of hyperthermic intraperitoneal chemotherapy (HIPEC) to interval cytoreductive surgery (CRS) improved recurrence-free and overall survival in patients with stage III ovarian cancer. We studied the cost effectiveness of the addition of HIPEC to interval CRS in patients with ovarian cancer. PATIENTS AND METHODS We constructed a Markov health-state transition model to measure costs and clinical outcomes. Transition probabilities were deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The incremental costeffectiveness ratio, expressed as euros per quality-adjusted life-year, was below the willingness-to-pay threshold in the Netherlands, indicating interval debulking surgery with HIPEC is cost effective for these patients. These results support the reimbursement of costs for patients treated with interval debulking surgery and HIPEC in countries with similar healthcare systems (19).…”
Section: Hipec For Primary Advanced Ovarian Cancersupporting
confidence: 74%
“…The incremental costeffectiveness ratio, expressed as euros per quality-adjusted life-year, was below the willingness-to-pay threshold in the Netherlands, indicating interval debulking surgery with HIPEC is cost effective for these patients. These results support the reimbursement of costs for patients treated with interval debulking surgery and HIPEC in countries with similar healthcare systems (19).…”
Section: Hipec For Primary Advanced Ovarian Cancersupporting
confidence: 74%
“…The incremental cost-effectiveness ratio amounted to €28,299 per QALY, which is under the willingness-to-pay threshold of €80,000 in the Netherlands. 43 These results lend support for reimbursing the costs of treating these patients with interval CRS and HIPEC in countries with comparable health care systems.…”
Section: Existing Evidencementioning
confidence: 73%
“…One actual PCI threshold that has been advocated is a maximum of 18 points, and – not surprisingly – the lower the threshold was, the more favorable the oncologic outcome. A recent study found that the addition of HIPEC to CRS does not negatively impact the health-related quality of life [27], and two recent studies showed CRS and HIPEC to be cost-effective in two different countries [28, 29].…”
Section: Discussionmentioning
confidence: 99%